2022
DOI: 10.3389/fnins.2022.1011103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketamine on cognition, anxiety, and social functioning in adults with psychiatric disorders: A systematic review and meta-analysis

Abstract: BackgroundIt has been shown that ketamine can improve suicidality and depression. Evidence for other dimensions of psychopathology is lacking. We undertook a systematic review to investigate the effect of ketamine on cognition, anxiety, quality of life, and social functioning in adults with psychiatric disorders.MethodsPubMed (Medline), Scopus, PsycINFO, and EMBASE were searched up to April 2022. Randomized controlled trials (RCTs) on ketamine [or its S (+) enantiomer] reporting data on cognition, anxiety, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…This report includes 4 SRs, [30][31][32][33] 7 RCTs, [34][35][36][37][38][39][40] 1 economic evaluation, 41 and 2 evidence-based guidelines. 42,43 Study selection details are presented in Appendix 1.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 4 more Smart Citations
“…This report includes 4 SRs, [30][31][32][33] 7 RCTs, [34][35][36][37][38][39][40] 1 economic evaluation, 41 and 2 evidence-based guidelines. 42,43 Study selection details are presented in Appendix 1.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…• 2 SRs 30,33 and 1 guideline 43 had broader inclusion criteria for the population than the present review, with 1 SR and the guideline 43 on major depressive disorder (MDD) and the other SR on psychiatric disorders. 33 We included findings specific to TRD 30,33,43 • the RCT by Harvey et al 36 was a substudy of the larger RCT by Loo et al 38 Different outcomes were reported in each trial; therefore, we included both studies in this Rapid Review. We did not include data from a third comparison group of healthy adults in the RCT by Harvey et al 36 • 2 RCTs 37,39 were authored by the same group of researchers.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations